Dynamic Treatment Effect Analysis of TV Effects on Child Cognitive Development - HUANG, Fali (Institutional Knowledge at Singapore Management University, 2007)
We investigate whether TV watching at ages 6-7 and 8-9 aﬀects cognitive development measured by math and reading scores at ages 8-9 using a rich childhood longitudinal sample from NLSY79. Dynamic panel data models are estimated to handle the unobserved child-speciﬁc factor, endogeneity of TV watching, and dynamic nature of the causal relation. A special emphasis is put on the last aspect where TV watching aﬀects cognitive development which in turn aﬀects the future TV watching. When this feedback occurs, it is not straightforward to identify and estimate the TV eﬀect. We adopt estimation methods available in the biostatistics literature which can deal with the feedback feature; we also apply the “standard” econometric panel data IV approaches. Overall, for math score at ages 8-9, we ﬁnd that watching TV for more than two hours per day during ages 6-9 has a negative total eﬀect mostly due to a large negative eﬀect of TV watching at the younger ages 6-7. For reading score, there are evidences that TV watching between 2-4 hours per day has a positive eﬀect whereas the eﬀect is negative outside this range. In both cases, however, the eﬀect magnitudes are economically small.